2011
DOI: 10.1017/s0954422410000326
|View full text |Cite
|
Sign up to set email alerts
|

The role of dietary nucleotides in single-stomached animals

Abstract: The transition from liquid to solid feed during weaning results in morphological, histological and microbial changes in the young animal's intestinal tract and often is associated with diarrhoea. The ban of in-feed antibiotics in pig production in the European Union has led to increasing interest in alternatives to overcome weaning-associated problems. Among others, nucleotides may have the potential to alleviate health impairments due to weaning. Nucleotides are natural components of the non-protein fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 101 publications
1
83
0
5
Order By: Relevance
“…It was recognized that the nucleic acid and nucleotides in YP contributed to the innate immune response. Consistently, Sauer et al (2011) found that weanling piglets fed nucleic acids for 2-4 weeks improved lymphocyte function and in vitro proliferative responses to a non-specific T-cell mitogen. Moreover, intestinal lymphocyte maturation and mRNA abundance of IL-6 and IL-8 were also enhanced by dietary nucleotides (Gil 2002).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…It was recognized that the nucleic acid and nucleotides in YP contributed to the innate immune response. Consistently, Sauer et al (2011) found that weanling piglets fed nucleic acids for 2-4 weeks improved lymphocyte function and in vitro proliferative responses to a non-specific T-cell mitogen. Moreover, intestinal lymphocyte maturation and mRNA abundance of IL-6 and IL-8 were also enhanced by dietary nucleotides (Gil 2002).…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, exogenous supply of nucleotides contributed to growth performance of piglets with nutritional role for maturation of some tissues such as lymphoid tissue and intestine in periods of intensive development (Sanchez-Pozo and Gil 2002). Exogenous nucleotides have been demonstrated to maintain the function of rapidly dividing tissues, stimulate innate immunity, and reduce the incidence of enteric diseases (Uauy 1994;Sauer et al 2011). Nutritionally, furthermore, it has been reported that YP had comparable nutrients digestibility as SDPP (Mateo and Stein 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Os NU exercem importantes funções no organismo, por serem precursores dos ácidos nucleicos (DNA e RNA), reguladores biológicos e fonte de energia (ATP) (LERNER e SHAMIR, 2000;SAUER et al, 2011) e podem ser sintetizados pela "via de novo", utilizando aminoácidos como precursores e com alto custo energético, ou pela "via de salvamento", a partir de produtos da digestão de ácidos nucléicos da dieta.…”
Section: Resultsunclassified
“…Considerando certos estados patológicos e períodos de limitada ingestão de nutrientes ou mesmo para tecidos de rápido crescimento, como o epitélio intestinal, os NU podem ser considerados, nutricionalmente, essenciais, pois, a síntese pela "via de novo" pode ser insuficiente (SAUER et al, 2011;HESS et al, 2012). Assim, sua presença nas dietas pode beneficiar a morfologia e função gastrointestinal, o sistema imunológico e a microbiota intestinal de animais monogástricos (SAUER et al, 2011).…”
Section: Resultsunclassified
See 1 more Smart Citation